FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU CARING PERAWAT DI RUANG RAWAT INAP IRINA C RSUP PROF. DR. R. D. KANDOU MANADO - Natalia Veronika Harahap; Ferlan Ansye Pondaag; Juwita Moreen Toar (JURNAL KEPERAWATAN, 2022)
Background: Caring behavior is one of the most influential factors in improving the quality of health care, especially nursing services. Purpose: To find out factors related to caring nurse behavior in the hospital of Irina C RSUP Prof. Dr. R. D. Kandou Manado. Methods: Quantitative study with a descriptive research design correlation with a cross sectional with executive nurse samples, technique of sampling total sampling, research instruments use individual factor questionnaires, organizational factors, psychological factors and a thoughtful nurse's behavior questionnaires developed by wolf and using spearman's statistical test. Results: The research suggests that there isa significant connection of each factor: skill ability (p=0,000, r= 0.487), leadership (p= 0.002, r= 0.313), organizational structure (p= 0.002, r= 0.348), work design (p= 0.005, r= 0.348), attitude (0.015, r= 0.317), and motivation (p= 0.003, r= 0.003) and caring behavior (p= 0.003). Conclusion: There is a link between the individual factors (skill skills), organizational factors (leadership, organizational structure, incentives, job design) and psychological factors (attitude and motivation) with the caring nurse behavior in the hospital Irina C RSUP Prof. Dr. R. D. Kandou Manado.